Peran Evaluasi Kinerja Guru dalam Meningkatkan Motivasi dan Profesionalisme Guru Disekolah - Nelfi Hermalinda; Yola Fitrian; Suci Natasha (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
Improving the quality of education is highly dependent on the professional and effective performance of teachers. This article integrates findings from various studies related to teacher performance evaluation, principal supervision, and teacher professionalism. The results of the study indicate that systematic teacher performance evaluation is able to identify weaknesses and provide opportunities for teacher competency development. In addition, the role of the principal as a supervisor and participatory leader contributes significantly to work motivation and improving teacher professionalism. Performance-based supervision is the main strategy in managing education to ensure optimal learning quality. Teacher work motivation is also found to be an important supporting factor in achieving better learning outcomes. The implication of the synergy between performance evaluation, principal supervision, and work motivation is the creation of an educational environment that is conducive to the development of teacher professionalism, which ultimately has an impact on improving the quality of education. This study provides recommendations for education stakeholders to strengthen the evaluation and supervision system in supporting sustainable teacher performance.